Predicting outcomes in rheumatoid arthritis related interstitial lung disease. Issue 1 (3rd January 2019) - Jacob, Joseph; Hirani, Nikhil; van Moorsel, Coline H.M.; Rajagopalan, Srinivasan; Murchison, John T.; van Es, Hendrik W.; Bartholmai, Brian J.; van Beek, Frouke T.; Struik, Marjolijn H.L.; Stewart, Gareth A.; Kokosi, Maria; Egashira, Ryoko; et al.
The aim of this study was to compare radiology-based prediction models in rheumatoid arthritis-related interstitial lung disease (RAILD) to identify patients with a progressive fibrosis phenotype. RAILD patients had computed tomography (CT) scans scored visually and using CALIPER and forced vital capacity (FVC) measurements. Outcomes were evaluated using three techniques, as follows. 1) Scleroderma system evaluating visual interstitial lung disease extent and FVC values; 2) Fleischner Society idiopathic pulmonary fibrosis (IPF) diagnostic guidelines applied to RAILD; and 3) CALIPER scores of vessel-related structures (VRS). Outcomes were compared to IPF patients. On univariable Cox analysis, all three staging systems strongly predicted outcome (scleroderma system hazard ratio (HR) 3.78, p=9×10 −5 ; Fleischner system HR 1.98, p=2×10 −3 ; and 4.4% VRS threshold HR 3.10, p=4×10 −4 ). When the scleroderma and Fleischner systems were combined, termed the progressive fibrotic system (C-statistic 0.71), they identified a patient subset (n=36) with a progressive fibrotic phenotype and similar 4-year survival to IPF. On multivariable analysis, with adjustment for patient age, sex and smoking status, when analysed alongside the progressive fibrotic system, the VRS threshold of 4.4% independently predicted outcome (model C-statistic 0.77). The combination of two visual CT-based staging systems identified 23% of an RAILD cohort with an IPF-like progressive fibrotic phenotype. The addition of a computer-derived VRS threshold further improved outcome prediction and model fit, beyond that encompassed by RAILD measures of disease severity and extent. Combining the scleroderma and Fleischner staging systems in RAILD identifies patients with an IPF-like progressive fibrotic phenotype. CALIPER VRS scores further improve model fit, beyond that encompassed by RAILD measures of disease severity and extent. http://ow.ly/SUcV30mmeYI